2014
DOI: 10.1590/1807-3107bor-2014.vol28.0046
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength of a calcium silicate-based sealer tested in bulk or with different main core materials

Abstract: Bond strength of a calcium silicatebased sealer tested in bulk or with different main core materials Abstract: The aim of this study was to evaluate the influence of a calcium silicate-based sealer (iRoot SP), with or without a core material, on bond strength to radicular dentin, in comparison with various contemporary root filling systems. Root canals of freshly extracted singlerooted teeth (n = 60) were instrumented using rotary instruments. The roots were randomly assigned to one of the following experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 29 publications
(28 reference statements)
4
37
0
Order By: Relevance
“…This fact, allied to the cohesion among sealer molecules, increases the resistance to removal and/or displacement from dentin, which can be translated as greater adhesion (24)(25)(26) . These results were in agreement with previous study comparing bond strength of a calcium silicate-based sealer tested in bulk or with different main core materials,and showed that IRoot SP and AH plus showing a high dislodgement resistance in push-out test than of MTA Fillapex (27) .…”
Section: Discussionsupporting
confidence: 93%
“…This fact, allied to the cohesion among sealer molecules, increases the resistance to removal and/or displacement from dentin, which can be translated as greater adhesion (24)(25)(26) . These results were in agreement with previous study comparing bond strength of a calcium silicate-based sealer tested in bulk or with different main core materials,and showed that IRoot SP and AH plus showing a high dislodgement resistance in push-out test than of MTA Fillapex (27) .…”
Section: Discussionsupporting
confidence: 93%
“…According to previous studies, root canal sealers significantly lower dislocation resistance values when used in main core rather than in bulk-filled form [23,43]. As stated in a previous study, deformation of the gutta-percha during the push-out test may lead incorrect measurements [44].…”
Section: Discussionmentioning
confidence: 74%
“…10 However, controversial results have been reported with respect to the adhesiveness of these sealers. 7,11,12 MTA Fillapex (Angelus, Londrina, Brazil) is a new calcium silicate-based sealer presenting low solubility and disintegration, 13 and good flow 3 and alkaline pH, 14 but it has a reduced bond strength when compared with AH Plus. 15,16 In addition to RCS, the root filling technique also may affect the quality of the bonding between the filling mass and the root dentin.…”
Section: 2mentioning
confidence: 99%